Quiet Quitting Among Healthcare Professionals: A Bibliometric and Content Analysis. - Hosgor, Haydar Kerem; Gun, Ibrahim (International Journal of Caring Sciences)
Background: Quiet quitting is becoming increasingly prevalent among the competent healthcare workforce, which serves as the driving force of the healthcare system, and this trend has negative implications for organizational outcomes. Objective: This study aims to examine publications on quiet quitting among healthcare professionals through bibliometric and content analysis. Method: The data for this qualitative study, which employs bibliometric and content analysis, were retrieved from the Web of Science database. The VOSviewer software was used for bibliometric analysis and visualization. Microsoft Excel was utilized for the categorization and graphical representation of the data obtained from the content analysis. Results: Within the scope of this study, 10 publications authored by 24 researchers were analyzed. It was noted that the earliest studies on quiet quitting among healthcare professionals date back to 2024. These publications appeared in seven different journals, with an average of 6.4 citations per journal. The journal with the highest number of citations was Healthcare, while the journals with the highest number of publications were Healthcare, Nursing Report, and AIMS Public Health. The most prolific and highly cited authors were identified as "Galanis," "Katsiroumpa," and "Moisoglou," with Greece being the most productive country in this research area. The most frequently used keywords were "quiet quitting" and "nurses." According to the content analysis, the most commonly examined variables alongside the quiet quitting scale were "job burnout" and "turnover intention." Additionally, all studies were found to be cross-sectional, and 70% of them included nurse participants. Conclusions: Quiet quitting is a relatively novel research topic in both national and international literature, indicating the need for more extensive empirical studies on the subject. Examining the phenomenon in relation to different variables and through international collaborations will provide new perspectives for researchers interested in this area.